Technology- enabled advance in the worlds of statistics, machine learning and data mining - Maindonald, John (New Zealand Science Review, 2011)
​Advances in digital computing continue to have large effects on all aspects of life and society, including science. These advances are possible because we have computer languages that translate directly into computational steps that can be implemented in computer hardware. Here, I draw attention to changes that are affecting the theory and practice of data analysis, with a focus on methodologies that feature in expositions of data mining and machine learning. The R language and system is playing an increasingly important role in making the new abilities readily accessible at the scientific workbench.